Why And How Children Are Used For War - Jermsittiparsert, Kittisak; Thanh Nguyen, Phong; Thuy To Nguyen, Quyen Le Hoang; Bich Huynh, Vy Dang; Shankar, K. (Opción, 2019)
The children are innocent and they have very soft heart which can be molded with any desired emotion. That is the reason some organizations are using children for transporting the secret information and documents in the war. The human rights already declared that the age recruitment will be eighteen. The age under than eighteen is prohibited. But there are many countries where the children from native parent or the mother and father belongs from any other country are occupying in the army. This research is focused on know how heartless some countries are and what are the outcomes of using children in the war. The children involved in using weapons, seeing violence puts directly impact on their emotions, mental development and decision taking abilities. One of the country is Afganistan where children are used as fighter and self killing sucide attackers. Even the United Nations also prepared an report where it was told that children are recruited by the Police department of Afgan.